Influenza Testing, Diagnosis, and Treatment in the Emergency Department in 2009–2010 and 2010–2011. (15th August 2013) - Peters, Timothy R.; Suerken, Cynthia K.; Snively, Beverly M.; Winslow, James E.; Nadkarni, Milan D.; Kribbs, Scott B.; Poehling, Katherine A.; Wilbur, Lee
Abstract Objectives The objective was to describe patterns of rapid influenza test ordering, diagnosis of influenza, and antiviral prescribing by the treating physician for children and adults presenting to emergency departments (EDs) with fever and acute respiratory symptoms in Winston‐Salem, North Carolina, over two influenza seasons. Methods The authors prospectively enrolled patients presenting to the ED with fever and acute respiratory symptoms for two influenza seasons: H1N1 pandemic of September 2009 through mid‐May 2010 and November 2010 through April 2011. Enrolled patients had nose or and throat swabs obtained and tested for influenza by viral culture and polymerase chain reaction (PCR) testing. Demographic information and medical history were obtained by patient or guardian report. Testing, treatment, and discharge diagnosis from the ED visit, as well as medical history and insurance status, were ascertained from chart review. Results Among 2, 293 eligible patients approached, 1, 657 (72%) were enrolled, of whom 38% were younger than 18 years, 47% were 18 to 49 years, and 15% were 50 years of age and older. Overall, 14% had culture‐ or PCR‐confirmed influenza. The odds of 1) rapid influenza test ordering, 2) a physician diagnosis of influenza, and 3) prescribing antiviral treatment during the ED visit were fourfold higher among patients with than without culture‐ or PCR‐confirmed influenza. The odds of rapid influenza test ordering were threefold lower in 2009/2010 than 2010/2011, whereas the odds of physician diagnosis of influenza and antiviral prescriptions were 2‐ and 3.5‐fold higher, respectively. Conclusions In 2009/2010 compared to 2010/2011, the odds of rapid influenza test ordering were lower, whereas the odds of influenza‐specific discharge diagnoses and antiviral prescriptions were higher among patients presenting to the ED with culture/PCR‐confirmed influenza. These results demonstrated a gap between clinical practice and recommendations for the diagnosis and treatment of influenza from the Centers for Disease Control and Prevention (CDC).